Persepolis - Satrapi, Marjane (London : Vintage Books, 2006)
The intelligent and outspoken child of radical Marxists, and the great-granddaughter of Iran's last emperor, Satrapi bears witness to a childhood uniquely entwined with the history of her country. Persepolis paints an unforgettable portrait of daily life in Iran and of the bewildering contradictions between home life and public life. This is a beautiful and intimate story full of tragedy and humour-raw, honest and incredible illuminating.
Keywords: Satrapi, Marjane,1969$1 (BComic books, strips,s